Hybrid Electrospun Nanofibers as Electrocatalyst for Vanadium Redox Flow Batteries: Theory and Experiment. Issue 1 (8th January 2021) - Maleki, Mahboubeh; Tichter, Tim; El‐Nagar, Gumaa A.; Lauermann, Iver; Roth, Christina
Abstract: Selective modification of the morphology and intrinsic electrocatalytic activity of porous electrodes is urgently required to improve the performance of vanadium redox flow batteries (VRFBs). For this purpose, electrospinning was exploited to prepare high‐performance nanofiber‐based composites. Blends of polyacrylonitrile, polyacrylic acid, and polyaniline with carbon black were electrospun into a 3D free‐standing nanofibrous web, which was utilized as a novel electrode. By extending the recent theory of cyclic voltammetry at porous electrodes to account for interfacial double‐layer capacities, nonlinear effects of ohmic resistances, and parasitic reactions, we could quantitatively investigate non‐faradaic as well as desired and undesired faradaic current contributions. Combination of experimental and theoretical studies allowed a unique quantitative assessment of the intrinsic catalytic activity of selected electrode materials concerning the VO2 + /VO 2+ redox reaction. Abstract : In a spin : A vanadium redox flow battery (VRFB) electrode is prepared by blending polyacrylonitrile (PAN), polyacrylic acid (PAA), and polyaniline (PANi) with carbon black (CB) and electrospinning into a 3D free‐standing nanofibrous mat. The results show that this electrospun nanofibrous composite enhances the electron conductivity, the intrinsic catalytic activity, and electrochemical stability when employed as electrode for VRFBs.